Isolation of Brucella suis biovar 1 from a pig breeding farm in Brazil. Case Report - Massa, Rafael [UNESP]; Pinheiro da Silva, Glaucenyra Ceclia [UNESP]; Santos, Renata Ferreira dos [UNESP]; Samartino, Luis Ernesto; Mathias, Luis Antonio [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
The objective of this study was to confirm the occurrence of swine brucellosis by isolating Brucella suis from an outbreak that occurred in December 2012 in a Certified Pig Breeding Farm (Granja de Reprodutores Suinos Certificada, GRSC), in Guariba, Sao Paulo, Brazil. To this end, we collected the livers and spleens of seven stillborn piglets born to six different sows that had aborted. Furthermore, the stomach content from one piglet was also collected. The organs were prepared using sterile materials and seeded in Petri dishes containing Brucella agar with 5% rabbit serum medium. The routine tests confirmed that the B. suis biovar 1 strain was the causative agent. Therefore, the results showed that despite the reduced incidence of swine brucellosis caused by Brucella suis in the country, the causative agent of the disease is still present, able to reach herds with higher biosafety levels, threatening human and animal health.
Keywords: Isolation; Brucellosis; Swine